Jeremiah 6:13 and the Challenge of Prosperity Gospel in Contemporary Anglican Priesthood in Nigeria - Chindo, Obi C.; Umeanolue, Ikenna L. (Nigerian Journal of Arts and Humanities, 2023)
This study examined the challenge of prosperity gospel within the contemporary Anglican priesthood in Nigeria in the light of Jeremiah 6:13. In this Old Testament biblical text, prophet Jeremiah frowned at the level of greed found among the priests of his time which consequently led to their false dealing with God’s people which manifested in the exploitation and imposition of levies. Prosperity gospel is a gospel of materialism and success. It is a gospel that insists that followers of Christ are meant to have material possessions and blessings of health and wealth, as their right and inheritance for being Christians and that they can obtain these blessings through positive confessions of faith and the ‘sowing of seeds’, through the faithful payments of tithes and offerings, hence the emphasis on material things and giving. The discussion focuses more on the priests of the Anglican extraction, who are called for the caring and curing of souls by preaching the gospel of Christ without bias. However, the sudden quest for wealth and material possessions by some Anglican priests, which is largely caused by heavy financial obligations from the bishops, has resulted to loss of respect for the priests, and loss of membership of the Anglican faithful among others. The study however, suggested that there should be a reduction of quota on churches while the welfare package for the priests is reviewed among other things. The study used exegetical method of biblical studies to interpret the text of Jeremiah 6:13 and apply the exegetical message in the context of the contemporary Anglican priesthood in Nigeria.
free